Fontes de lipídios em dietas para juvenis de jundiá (Rhamdia quelen) - Gomes, Ricácio Luan Marques (2018)
The objective of the study was to evaluate animal and vegetable oils in juvenile diets of jundiás. A total of 300 fish (18.45 ± 1.22 g) were used, distributed in 20 net tanks of 1m3, arranged in a 200m2 masonry nursery. The diets formulated contained 3.0% soybean, sunflower, fish, canola and olive oil. At the end of the experimental period, the variables of productive performance, centesimal composition, intestinal histomorphometry, liver histology, plasma biochemistry and enzymatic activity were analyzed. The results were similar for the productive performance, however, the visceral fat index was higher for the diet containing sunflower oil (p <0.05). There was no difference (p> 0.05) for the variables of centesimal composition, intestinal histology and biochemical parameters. In hepatic histological evaluations, the fish fed with the soybean oil diet had a higher (p <0.05) number of hepatocytes. The animals fed with fish oil presented higher TBARS lipoperoxidation and higher GST enzyme activity (p <0.05). Therefore, it can be concluded that the different oils can be used to feed this species without any damage to the productive performance. It is not recommended to include sunflower oil, because it provides greater deposition of visceral fat.